EFL mentor teachers’ voices on mentoring practice: Strategies, challenges, and needs - Suryati, Nunung (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Mentoring is one of the important process a teacher should have since it is a key component in teacher education and professional development (Delaney, 2021). The present study is a part of a larger research project which explores student teachers’ and mentor teachers’ perspectives, experiences, as well as challenges encountered during the teaching practicums. This study adopted the Grounded-Theory method (Glaser, 1998) in which qualitative design is utilized. Qualitative approach was selected as the research aims to explore in-depth investigation regarding the experience of the mentor teachers during the teaching practicum. The findings of this study indicate that mentor teachers perceived their mentoring as satisfactory in several points. However, there are several aspects of the mentoring practice that they redeemed themselves as not satisfying. Future studies can be directed to discover mentors’ framework and their forms of mentoring practice. Studies investigating mentors’ approach and design in mentoring practice should also be conducted to understand their perception about mentoring practice.